2013
DOI: 10.1186/1472-6963-13-295
|View full text |Cite
|
Sign up to set email alerts
|

Public health communications and alert fatigue

Abstract: BackgroundHealth care providers play a significant role in large scale health emergency planning, detection, response, recovery and communication with the public. The effectiveness of health care providers in emergency preparedness and response roles depends, in part, on public health agencies communicating information in a way that maximizes the likelihood that the message is delivered, received, deemed credible and, when appropriate, acted on. However, during an emergency, health care providers can become in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 19 publications
2
77
1
Order By: Relevance
“…Increasing the number of threshold events may result in alert fatigue, and tiered approaches should be balanced against this possibility. 25 Although there is some evidence of benefit from public health interventions for heatwaves that have a major health impact, the magnitude of this benefit is uncertain -potentially more so for moderate events. 26 More research is required to determine the appropriate response to these common moderate heatwave events and their utility.…”
Section: Scalley Et Al Articlementioning
confidence: 99%
“…Increasing the number of threshold events may result in alert fatigue, and tiered approaches should be balanced against this possibility. 25 Although there is some evidence of benefit from public health interventions for heatwaves that have a major health impact, the magnitude of this benefit is uncertain -potentially more so for moderate events. 26 More research is required to determine the appropriate response to these common moderate heatwave events and their utility.…”
Section: Scalley Et Al Articlementioning
confidence: 99%
“…Alert fatigue is more likely when endogenous recognition and exogenous recognition are in conflict (i.e., an alert occurs for a condition of which a provider is already aware). Additionally, alert fatigue can occur due simply to the proliferation of alerts, even if they are informative (20,29,30). This is well documented in the intensive care unit, where frequent chimes, buzzers, and beeping fade quickly into background obscurity.…”
Section: Potential Harms Of Alertingmentioning
confidence: 99%
“…This manner of characterizing aerosol concentrations remains in common practice today, although it does not have a fundamental basis in terms of physiological response. More recent studies have shown that total aerosolized surface area tends to more strongly correlate with adverse health effects [33][34][35]. Apart from the appropriateness of mass concentration as an exposure metric, the situation presents a challenge because the majority of measurement techniques do not measure mass directly.…”
Section: The Fire Fighting Environment and Associated Measurementsmentioning
confidence: 99%